Quality Standards for Sample Collection in Coagulation Testing - Lippi, Giuseppe; Salvagno, Gian Luca; Montagnana, Martina; Lima-Oliveira, Gabriel; Guidi, Gian Cesare; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2012)
Preanalytical activities, especially those directly connected with blood sample collection and handling, are the most vulnerable steps throughout the testing process. The receipt of unsuitable samples is commonplace in laboratory practice and represents a serious problem, given the reliability of test results can be adversely compromised following analysis of these specimens. The basic criteria for an appropriate and safe venipuncture are nearly identical to those used for collecting blood for clinical chemistry and immunochemistry testing, and entail proper patient identification, use of the correct technique, as well as appropriate devices and needles. There are, however, some peculiar aspects, which are deemed to be particularly critical when collecting quality specimens for clot-based tests, and these require clearer recognition. These include prevention of prolonged venous stasis, collection of nonhemolyzed specimens, order of draw, and appropriate filling and mixing of the primary collection tubes. All of these important preanalytical issues are discussed in this article, and evidence-based suggestions as well as recommendations on how to obtain a high-quality sample for coagulation testing are also illustrated. We have also performed an investigation aimed to identify variation of test results due to underfilling of primary blood tubes, and have identified a clinically significant bias in test results when tubes are drawn at less than 89% of total fill for activated partial thromboplastin time, less than 78% for fibrinogen, and less than 67% for coagulation factor VIII, whereas prothrombin time and activated protein C resistance remain relatively reliable even in tubes drawn at 67% of the nominal volume.
Keywords: preanalytical variability; coagulation testing; prothrombin time; activated partial thromboplastin time; laboratory errors